Exact solutions of the korteweg & vries equation - Chong Juhn Yung, 1991- author; Ong, Chee Tiong, supervisor; Fakulti Sains (2015)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2015